Specificity of family education concept implementation of H. Skovoroda in the novel «Maria with warmwood in the end of the century» (Maria z polynom u kintsi stolittia) written by V. Yavorivskyi (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article presents an underresearched perspective of influence of G.Skovoroda’s theories about «cognate» labour (business) and family upbringing to the artistic concept of the novel «Maria with sage in the end of the century» by V.Yavorivskiy. The main accent is guided to open the author’s interpretation of the national tragedy of Ukrainians following the anthropogenic disaster at the Chornobyl Nuclear Plant in April 1986.
Keywords: redemption; «cognate» labour (business); national education; family upbringing; catharsis